Prescribing non-steroidal anti-inflammatory drugs: a prospective study of patients' preference. Issue 677 (March 1982) - Scott, D. L.; Low-Beer, T. S.; Roden, S.; Takavarasha, L.
Abstract : Thirty-six patients with rheumatoid arthritis were allocated at random to one of 3 groups prescribed 4 different non-steroidal anti-inflammatory drugs (NSAID). Each drug was given for one week over 4 consecutive weeks in a balanced order. The patients were then asked to select one NSAID for continuation therapy and were followed-up 6 months later. The success of the patient selection method was compared with that of physician selection by retrospectively surveying NSAID prescribing in 164 patients attending 2 other rheumatology units over a 5-year period. Only 72% of patients in the prospective study felt able to choose one of the NSAIDs and 31% of these had discontinued the chosen drug within 6 months. In the retrospective study, 40% changed their NSAID within 6 months.